2006
DOI: 10.1177/1359786806066055
|View full text |Cite
|
Sign up to set email alerts
|

The neuronal noradrenaline transporter, anxiety and cardiovascular disease

Abstract: Panic disorder can serve as a clinical model for testing whether mental stress can cause heart disease. Potential neural mechanisms of cardiac risk are the sympathetic activation during panic attacks, continuing release of adrenaline as a co-transmitter in the cardiac sympathetic nerves, and impairment of noradrenaline neuronal reuptake, augmenting sympathetic neural respnses. The phenotype of impaired neuronal reuptake of noradrenaline: an epigenetic mechanism? We suspect that this phenotype, in sensitizing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 27 publications
1
61
1
1
Order By: Relevance
“…Several studies have reported that patients with POTS have comorbid psychiatric symptoms, particularly anxiety and panic disorder 8 25. Using the Structured Clinical Interview for DSM-IV axis I disorders, we found that there was no significant difference in lifetime prevalence of major depressive disorder in patients with POTS compared with a general population sample 17.…”
Section: Discussioncontrasting
confidence: 50%
“…Several studies have reported that patients with POTS have comorbid psychiatric symptoms, particularly anxiety and panic disorder 8 25. Using the Structured Clinical Interview for DSM-IV axis I disorders, we found that there was no significant difference in lifetime prevalence of major depressive disorder in patients with POTS compared with a general population sample 17.…”
Section: Discussioncontrasting
confidence: 50%
“…Aberrant (not mental) stimuli can reach either the parasympathetic or sympathetic components of the autonomic component of concrete mind, such that our mental existence experiences either an unexplainable (free-floating) anxiety (unjustified by mental data), or low mood and behavior/ aversion to activity in the form of depression (23,24).…”
Section: Abstract and Concrete Mindsmentioning
confidence: 99%
“…Another line of evidence suggests that cardiac sensitization by faulty neuronal noradrenaline uptake might be the primary cause for the increased risk for sudden cardiac death in patients with panic disorder (Esler et al, 2006). Panic disorder affects 2-5% of the general population, is associated with cardiac symptoms, and prospective epidemiologic studies suggest an association between (phobic) anxiety, fatal coronary heart disease, and in particular sudden cardiac death (Kawachi et al, 1994a(Kawachi et al, , 1994b.…”
Section: Catecholamine Reuptakementioning
confidence: 99%
“…In patients with panic disorder, sympathetic nervous activity and adrenal medullary activity as measured by clinical microneurography were increased during panic attacks, and epinephrine spillover from the heart was elevated at rest (Wilkinson et al, 1998;Esler et al, 2004). These phenomena were not due to loss of function mutations in the coding region of the norepinephrine transporter gene, but could be traced back to hypermethylation in its promotor region leading to gene silencing (Esler et al, 2006). Thus, a faulty catecholamine reuptake associated with panic disorder might confer a particularly high risk to a susceptible human subpopulation to experience sudden cardiac death due to cardiac sensitization in the presence of halocarbons.…”
Section: Catecholamine Reuptakementioning
confidence: 99%